(untitled) (Bangladesh Journal of Pharmacology, 2022)
The objectives of the study were to investigate the analgesic, antianxiety and sedative effects of Pistacia lentiscus essential oil from fruits in mice. The antinociceptive effect was evaluated using three animal models such as writhing, hot plate, and formalin tests. While the sedative and antianxiety effects were evaluated using thiopental-induced sleeping time, elevated plus maze, hole-board, and open field assays. The essential oil possessed a strong antinociceptive effect at all doses. This effect was undone when animals were pretreated with naloxone and yohimbine in the neurogenic phase whereas atropine and glibenclamide were in the inflammation phase (formalin test). The administration of essential oil increased the latency of sleeping and extended time of sleeping in the thiopental test. On the other hand, essential oil possessed an anxiolytic effect. However, pretreatment with flumazenil reversed the effect indicating the possible implication of GABAA receptors.